Towards a Model for Encoding Correspondence in the TEI: Developing and Implementing - Peter Stadler; Marcel Illetschko; Sabine Seifert (Journal of the Text Encoding Initiative)
The encoding of letters has a long tradition in the TEI but there have been no official recommendations in the TEI Guidelines on how to deal with correspondence. Two TEI customizations present exemplary models: DALF: Digital Archive of Letters in Flanders and Carl Maria von Weber—Collected Works (WeGA). These were the basis of the work of the TEI Correspondence Special Interest Group that formed a task force—consisting of the three authors of this article—for developing encoding guidelines. This article discusses correspondence theory in brief, letters as an act of communication, and how these aspects of correspondence can be expressed by TEI entities. The development of the communication-oriented concept of correspondence and its direct implementation in correspondence-specific metadata structures will be discussed. Central is the new wrapper element (correspondence description), which stores key metadata about the encoded piece of correspondence. After addressing this first question of how one should encode correspondence with the TEI, we will discuss the question of linking and interchange between projects and editions dealing with correspondence material. To facilitate this, the Correspondence Metadata Interchange (CMI) format has been developed by the TEI Correspondence SIG’s task force as a subset of . Finally, we will describe some organizational difficulties in implementing the new elements and encoding model into the TEI Guidelines in 2015.